Conditional KCa3.1-transgene induction in murine skin produces pruritic eczematous dermatitis with severe epidermal hyperplasia and hyperkeratosis. - Javier Lozano-Gerona; Aida Oliván-Viguera; Pablo Delgado-Wicke; Vikrant Singh; Brandon M Brown; Elena Tapia-Casellas; Esther Pueyo; Marta Sofía Valero; Ángel-Luis Garcia-Otín; Pilar Giraldo; Edgar Abarca-Lachen; Joaquín C Surra; et al. (PLoS ONE)
Ion channels have recently attracted attention as potential mediators of skin disease. Here, we explored the consequences of genetically encoded induction of the cell volume-regulating Ca2+-activated KCa3.1 channel (Kcnn4) for murine epidermal homeostasis. Doxycycline-treated mice harboring the KCa3.1+-transgene under the control of the reverse tetracycline-sensitive transactivator (rtTA) showed 800-fold channel overexpression above basal levels in the skin and solid KCa3.1-currents in keratinocytes. This overexpression resulted in epidermal spongiosis, progressive epidermal hyperplasia and hyperkeratosis, itch and ulcers. The condition was accompanied by production of the pro-proliferative and pro-inflammatory cytokines, IL-β1 (60-fold), IL-6 (33-fold), and TNFα (26-fold) in the skin. Treatment of mice with the KCa3.1-selective blocker, Senicapoc, significantly suppressed spongiosis and hyperplasia, as well as induction of IL-β1 (-88%) and IL-6 (-90%). In conclusion, KCa3.1-induction in the epidermis caused expression of pro-proliferative cytokines leading to spongiosis, hyperplasia and hyperkeratosis. This skin condition resembles pathological features of eczematous dermatitis and identifies KCa3.1 as a regulator of epidermal homeostasis and spongiosis, and as a potential therapeutic target.